Influence of the magnetised sheath on the redeposition location of sputtered tungsten and its effect on the net erosion. (August 2017) - Mellet, N.; Gunn, J.P.; Pégourié, B.; Hakola, A.; Airila, M.; Marandet, Y.; Roubin, P.
Highlights: 1D and 2D modelling of tungsten redeposition based on self-consistently calculated sheath potential is proposed. The local impurity migration dependence on plasma parameters like electron density and temperature is investigated. Different models are studied allowing to isolate the different effects like ExB drift. Abstract: The effect of the magnetised sheath on tungsten migration and its consequences on net erosion of tungsten plasma facing components are investigated. This study points out a strong effect of theE ×B drift on the redeposition location as well as a rapid redeposition of the ejected particles that are ionised close to the surface. A plasma parameter study shows that the migration direction is changed at ≈ 10 eV from opposite toE ×B drift at low electron temperature to the same direction asE ×B at high electron temperature. Different models have been considered in the case of plasma parameter gradients that are also at the source of a component of the electric field parallel to the surface. New features are observed like an enhanced net erosion peak at the strike point if only the component of the electric field towards the surface is taken into account. When the component parallel to the surface that drives the particles away from or towards the surface is considered, a very different net erosion picture is obtained: a net erosion peak exists between two net deposition regions. This points out the importance of incorporating this effect in simulations.